Assessment of muscle volume using magnetic resonance imaging (MRI) in football players after hamstring injuries. Issue 9 (2nd September 2022) - Mühlenfeld, Nils; Steendahl, Ida Bo; Berthold, Daniel P.; Meyer, Tim; Hauser, Thomas; Wagner, Nils; Sander, Anna-Lena; Marzi, Ingo; Kaltenbach, Benjamin; Yel, Ibrahim; Vogl, Thomas; Eichler, Katrin
ABSTRACT: Muscle injuries of the hamstrings are among the most frequent in football and a main cause for significant time away from training and competition. The purpose of this study was to prospectively evaluate the loss of muscle volume in recreational football players three and six weeks after initial trauma. We hypothesized that significant muscle volume loss occurs within 6 weeks after the initial injury event. Twenty recreational football players (mean-age=25 ± 4years; mean-height=181 ± 8cm; mean-weight=81 ± 10kg) with type3a (minor partial muscle tear) and type3b (moderate partial muscle tear) injuries were included. Muscle volume was determined using established methods for the hamstrings and the quadriceps femoris muscle within 3 days and after 3 and 6 weeks following the initial injury. The injured hamstrings lost 6.5% (mean=64 cm 3 (95%CI=31–98 cm 3 ), p <0.001), the healthy hamstrings lost 2.1% (mean=21 cm 3 (3–44 cm 3 ), p =0.096) of muscle volume after six weeks. The quadriceps in the injured leg lost 3.8% (mean=78 cm 3 (51–104 cm 3 ), p <0.001) and 4.5% (83 cm 3 (45–121 cm 3 ), p <0.001) in the healthy leg. Muscle volume loss inversely correlated with activity levels in the healthy leg for the quadriceps (r=0.96 (0.90–0.98); R 2 =0.92; p <0.001) and the hamstrings (r=0.72 (0.40–0.88); R 2 =0.51; p <0.001), as well as the quadriceps in the injured leg (r=0.70 (0.37–0.87); R 2 =0.49; p <0.001), but not the injured hamstrings. Muscle volume ratio of hamstrings to quadriceps in the control limb was 0.52 ± 0.06 and 0.53 ± 0.06 in the injured leg. The rehabilitation period of six weeks did not have a relevant negative or a positive effect on ratios. Significant muscle volume loss in the upper thigh occurs in recreational soccer players within three, and within six weeks after a hamstring injury and lies between 2% and 7%.